Determinants of consistent and emerging food insecurity in Cavite, the Philippines, during the COVID-19 Pandemic - Guirindola, Mildred O.; Sobremisana, Marissa J.; Pacardo, Enrique P.; Barba, Corazon VC.; Silva, Ma. Esmeralda C.; Guirindola, Ruel B. (2025)
Food insecurity in the Philippines persists even without the pandemic. It is important to investigate how a crisis – particularly the COVID-19 pandemic – can exacerbate food insecurity, especially among the vulnerable segments of the population. This cross-sectional study examined the impact of the COVID-19 pandemic on the food security of 1,050 households with varied socioeconomic characteristics in the Province of Cavite. Logistic regression analysis was used to identify the socio-ecological predictors of consistent and emerging food insecurity. Findings indicate that households with five or more members (OR = 1.8, p = 0.003), with pre-pandemic income below PHP 10,000 (OR = 2.5, p < 0.001), and have household heads with lower educational attainment [at least elementary (OR = 3.3, p = 0.003) and at least high school (OR = 2.6, p = 0.005)] were more likely to be consistently food-insecure. Households who are members of the Pantawid Pamilyang Pilipino Program (OR = 1.7, p = 0.014), obtained food in community pantries (OR = 1.8, p = 0.002), and from 4th class areas (OR = 2.3, p = 0.029) were also twice likely to be consistently food-insecure. Households at risk of emerging food insecurity during the pandemic were those
with lesser income during the general community quarantine (OR = 3.3, p < 0.001), and headed by those who attained at least elementary (OR = 3.3, p = 0.017) and high school (OR = 2.6, p = 0.033) education. Long-term food shocks like the COVID-19 pandemic can trigger and even further aggravate the existing food insecurity. The study adds to the existing body of knowledge on how a protracted disaster can worsen and instigate emerging food-insecure households. Study findings can be used in the development or refinement of existing food policies to encourage local food production and improvement of the local food environment in preparation for future food shocks.
Keywords: COVID-19 pandemic; Food; food insecurity